2015
DOI: 10.1021/ct500958p
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale GW Calculations

Abstract: We present GW calculations of molecules, ordered and disordered solids and interfaces, which employ an efficient contour deformation technique for frequency integration and do not require the explicit evaluation of virtual electronic states nor the inversion of dielectric matrices. We also present a parallel implementation of the algorithm, which takes advantage of separable expressions of both the single particle Green's function and the screened Coulomb interaction. The method can be used starting from densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
467
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(479 citation statements)
references
References 113 publications
12
467
0
Order By: Relevance
“…[313][314][315] However, in view of the on-going development of more efficient QM algorithms 179,[316][317][318][319] in conjunction with the use of graphics processing units 124,318,320,321 (GPUs), this limitation may be overcome in the near future. The calculation for anions is of particular interest considering that the accurate calculation of salt (cation plus anion) hydration free energies, which are not elusive quantities (just as the cation-to-cation difference considered here), would represent an important further validation of the present QM/MM methodology.…”
Section: Discussionmentioning
confidence: 99%
“…[313][314][315] However, in view of the on-going development of more efficient QM algorithms 179,[316][317][318][319] in conjunction with the use of graphics processing units 124,318,320,321 (GPUs), this limitation may be overcome in the near future. The calculation for anions is of particular interest considering that the accurate calculation of salt (cation plus anion) hydration free energies, which are not elusive quantities (just as the cation-to-cation difference considered here), would represent an important further validation of the present QM/MM methodology.…”
Section: Discussionmentioning
confidence: 99%
“…In general a real time or real frequency one-body Green's function is a function used to describe spectral properties such as ionization potentials, electron affinities, or the single-particle spectral function. Methods such as the random phase approximation (RPA) and GW usually express the Green's function using real frequencies to obtain spectra at zero temperature [37,38]. While, in general, the real frequency Green's function is an exponentially decaying function of frequency, it is very difficult to employ it in iterative methods such as DMFT or other embedding methods such as self-energy embedding theory (SEET) [39,40] since iterating usually requires pole shifting algorithms [41][42][43].…”
Section: Theorymentioning
confidence: 99%
“…20 This method has been shown to 5 provide quantitative predictions for the quasi-particle (QP) spectrum of organic and inorganic systems. 18,[21][22][23][24] However, not only is GW computationally much more demanding than DFT, the fact that it is typically employed non-self-consistently also leads to a significant starting-point dependence. [25][26][27][28][29][30][31] For the case of the pentacene molecule, for example, it has been found that nonself-consistent G 0 W 0 calculations based on a (semi-)local DFT starting point underestimate the fundamental gap E g in the gas phase by as much as 0.7 eV, while E g calculated at the same level of theory for the pentacene crystal are found in good agreement with the experimentally determined solid-state E g , likely due to a fortuitous cancelation of errors.…”
mentioning
confidence: 99%